Determining elastic constants of poplar wood (Populus deltoides) by ultrasonic waves and its application in the finite element analysis. Issue 6 (2nd November 2022) - Zahedi, Meysam; Kazemi Najafi, Saeed; Füssl, Josef; Elyasi, Majid
ABSTRACT: In simulation of wood mechanical behaviors, it is imperative to define elastic engineering parameters of the wood (three Young's moduli, three shear moduli and six Poisson's ratios). As regards, the determination of a set of nine independent elastic constants of wood by the experimental method is expensive and laborious and requires several specimens and test equipment and the literature is very rare and has a wide range in data. In this study, elastic engineering parameters of poplar wood ( Populus deltoides ) were determined by applying the ultrasonic waves and their first-ever application as input data in simulation of mechanical behavior of the poplar wood. Ultrasonic velocity measurements give a chance for the direct determination of the all orthotropic elastic constants using only little small stresses to the wood material. The commercial finite element program ABAQUS TM software package was used to model and analyze as linear orthotropic elastic materials. For validating the applicability and better and more accurate evaluation of engineering parameters were determined by ultrasonic wave propagation in simulation, both three-point bending and uniaxial tensile tests were examined. The ultrasonic technique for determination of elastic engineering parameters of poplar wood, as input data in the finite element method, leads to a very close correlation with the experiment results, which turns out that these data are reliable and applicable for the simulation of wood behaviors.